Studying the anti-cancer mechanisms of acetyltanshinone IIA and discovering apoptosis-inducing compounds from traditional Chinese medicine - Yu, Ting (2014)
Breast cancer is a major type of cancer in women which caused 460,000 deaths worldwide in 2008. Breast cancer can be classified into three types based on their receptor status: ER positive: express estrogen receptor (70%); HER2 positive: over-express human epidermal growth factor receptor 2 (20%); triple negative: do not express ER, HER2 and progesterone receptor (15-25%). Although hormone therapy using tamoxifen and aromatase inhibitors and HER2 therapy using Herceptin and lapatinib have been developed, they have limitations including non-responsive and drug resistance. Thus there is a need to develop new drug candidates that can target ER positive and HER2 over-expressing breast cancers. Recently we have found a new agent, acetyltanshinone IIA (ATA), which is a small molecular weight compound derived from herbal medicine. In our previous study, we found that ATA almost completely inhibited the growth of xenografted tumor from human melanoma MDA-MB-435 cells in nude mice. In current study, ATA was found to have potent growth inhibitory effect in breast cancer cells that are either ER positive or express a high level of HER2 protein. The results of mechanism study suggest that ATA may inhibit ER positive cell growth by binding to ERα, triggering ERα down-regulation and reducing ERα-responsible gene expression. ATA was also found to inhibit HER2 over-expressing cell proliferation by reducing the level of HER2 protein. The most significant novelty of ATA as a new anticancer agent is that it can reduce the protein levels of both ERα and HER2. ATA shall thus have the potential to treat breast cancers which are not responsive or resistant to the current ER or HER2 therapies. Another part of this thesis was to search apoptosis-inducing agents from Chinese herbal medicines as potential anti-cancer agents. We examined three kinds of plants from Garcinia genus: Garcinia paucinervis, Garcinia multiflora and Garcinia oligantha. Thirty four compounds in total were isolated from these three plants. HeLa-C3 cells, which have been genetically engineered to produce a ﬂuorescent biosensor capable of detecting caspase-3 activation, were used to determine the apoptosis inducing effect of these isolated compounds. Among 19 compounds extracted from Garcinia paucinervi, eight compounds were found to activate caspase-3 in HeLa-C3 cells within 72 h at the concentration of 25 µM. MTT results show that paucinervin B has the strongest inhibitory effect against HeLa cell growth with the IC50 of 9.5 μM. Among ten compounds isolated from Garcinia multiflora, three compounds showed apoptosis-inducing effect at the concentration of 25 µM. Further studies carried on the five compounds isolated from Garcinia oligantha showed that this plant had the strongest anti-cancer effect, as all these five compounds could induce cell apoptosis at 10 μM or even lower concentrations. Moreover, the values of IC50 were measured for all five compounds on HeLa cells using the MTT assay. Among them, gaudichaudione H had the lowest IC50 value of 0.90 μM, while the other four compounds had IC50 values of 1.58, 1.52, 4.15, and 7.82 μM, respectively. Using this caspase sensor-based high throughput screening platform, we efficiently identified compounds with strong apoptosis-inducing effect and high lethality against cancer cells. The most potent agents can be further studied and may have the potential to be developed into new anticancer drugs.